Socioeconomic effects of farmer-pastoralist conflict on agricultural extension service delivery in Oyo State, Nigeria (2015)
The study examined the socio - economic effect of farmer-pastoralist conflict on family farming in Oyo State, Nigeria. Multi-stage sampling technique was used to select to 60 farmers and 60 pastoralists for the research and were interviewed with structured questionnaire. Results showed that a little above half (52.6%) were between the ages of 30-50 years. The majority (63.3%) had household size of 5-9 members. Crop damage (63.3%) and indiscriminate bush burning (46.7%) were considered the most common causes of conflict between farmers and pastoralists. The majority (71%) of farmers suffer economic losses from farmer-pastoralist conflicts. About seventy five percent of farmers used more of problem-oriented (e.g. early harvesting/stock disposal) coping strategies while the majority of herdsmen (73%) used more of emotion-oriented strategies (e.g. use of charms/Vengeance. There was a significant difference (p=0.000) in socio-economic losses among farmers and pastoralists. Farmers are the worst hit of Farmer-pastoralist conflicts as it affects their family farming. Setting up of a three-tier farmer-herdsmen conflict management committee is recommended.